2014
DOI: 10.1126/scisignal.2005146
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-Wide Identification of SUMO2 Modification Sites

Abstract: Posttranslational modification with small ubiquitin-like modifiers (SUMOs) alters the function of proteins involved in diverse cellular processes. SUMO-specific enzymes conjugate SUMOs to lysine residues in target proteins. Although proteomic studies have identified hundreds of sumoylated substrates, methods to identify the modified lysines on a proteomic scale are lacking. We developed a method that enabled proteome-wide identification of sumoylated lysines that involves the expression of polyhistidine (6His)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
237
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(252 citation statements)
references
References 60 publications
15
237
0
Order By: Relevance
“…In agreement with our observations, a proteome-wide analysis recently identified K422 of endogenous FKBP51 as a putative SUMOylated site, 40 thus strengthening our findings.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our observations, a proteome-wide analysis recently identified K422 of endogenous FKBP51 as a putative SUMOylated site, 40 thus strengthening our findings.…”
Section: Discussionsupporting
confidence: 92%
“…The independent confirmation of SUMOylation of K136 by Tammsalu et al 37 , in addition to the absence of changes in the ubiquitylation of CDC73 K136 on MG132 treatment, support a role for SUMOylation in the nuclear retention of CDC73. This finding is consistent with a recent study on the E1 SUMOactivating enzyme SAE2, indicating that SUMOylation of several residues located within the NLS and adjacent to the NLS regions was required for the nuclear retention of SAE2, whereas the nonSUMOylatable form of SAE2 was rapidly exported to the cytoplasm 40 .…”
Section: Cdc73 Sumoylation Affects Its Nucleocytoplasmic Localizationmentioning
confidence: 59%
“…Indeed, a report published during the review of this manuscript identified K136, K301 and K385 as SUMOylated residues on CDC73 (ref. 37). It is noteworthy that a recent large-scale proteomics study performed on MG132-treated Jurkat cells identified 12 ubiquitylation sites on CDC73, of which 4 sites were identified in our study (K136, K161, K198 and K283) 38 .…”
Section: Cdc73 Sumoylation Affects Its Nucleocytoplasmic Localizationmentioning
confidence: 74%
“…Phosphorylation is a prerequisite for SUMOylation, which in turn promotes polyubiquitylation as a third posttranslational modification and eventually leads to degradation of the protein at the end of S phase, when it is no longer needed. It would be interesting to overlap the targets of cyclindependent kinases with known SUMO substrates, specifically as recent advances in proteomic approaches allow us to identify both phosphorylation and SUMOylation sites [48][49][50][51][52]. This might lend insight into the substrates that are co-regulated by SUMOylation and CDKs.…”
Section: Sumoylation and Cyclin-dependent Kinases In Concertmentioning
confidence: 99%